The school education, ritual customs, and reciprocity associated with self-regulating hand hygiene practices during COVID-19 in Japan - Sun Youn Lee; Shusaku Sasaki; Hirofumi Kurokawa; Fumio Ohtake (BMC, 2022)
Abstract Background The role of social ties, other-regarding preferences, and cultural traits in boosting community resilience and minimizing citizens' vulnerability to crises such as COVID-19 is increasingly being recognized. However, little is presently known about the possible routes through which such personal preferences and cultural norms pertinent to social behaviors are formulated. Thus, in this paper, factors that can be potentially associated with individuals to self-regulate strict hand hygiene practices before the pandemic, during the state of emergency, and after the state of emergency was lifted in Japan are investigated. Focus is given to the handwashing education in primary school, a cultural practice originating from the old Shinto tradition, and individuals' reciprocal inclinations. As people in Japan are known to be highly conscious of hygiene in all aspects of their daily life and are less likely to contract an infection, evidence obtained in this specific context could contribute to the better understanding of individuals' health-related behaviors in general, and during crises in particular. Methods Using the data derived from a four-wave nationwide longitudinal online survey, we examined the extent to which elementary school education, childhood cultural experiences at shrines, and individual other-regarding preferences are associated with self-regulating hand hygiene practices prior to the pandemic and people's efforts to comply with the government-imposed measures aimed at preventing the spread of COVID-19 infection during the state of emergency. We also investigated the long-term trends in the relationships among these factors (i.e., after the abolishment of the state of emergency) using panel data. Results Our findings reveal that childhood education and cultural experiences related to handwashing practices, as well as reciprocal inclinations, are significantly associated with Japanese attitudes toward personal hygiene (beyond handwashing practices) prior to, during, and after the state of emergency. In recognition of the possible effects of recall bias and measurement errors, several important attempts to mitigate these issues were made to strengthen the value of our findings. Conclusions The importance of school education received during childhood, as well as culture and other-regarding preferences, in the individual attitudes toward hand hygiene in adulthood highlighted in this study contributes to the better understanding of the role that these factors play in the variations in voluntary compliance with strict hand hygiene practices before and during an uncertain and prolonged crisis.